(untitled) (Bangladesh Journal of Botany, 2020)
Longer photoperiods in the form of night break (NB) were applied in chrysanthemum to inhibit the flower bud differentiation for regulating the production and supply in the market. The present study reports the effect of three sources of light (Incandescent bulbs, compact fluorescent lights (CFL) and light emitting diodes-LED) as NB treatment on ten genotypes of Korean chrysanthemum for two years i.e. 2015 and 2016. The NB treatment with LED lights resulted in increased internodal length (8.20 and 9.00 mm), partitioning coefficient (30.50 and 31.50), number of stomata per unit area (56.08 and 56.87), anthocyanins (8.99 and 9.16 mg/g) and carotenoids (28.11 and 28.39 mg/g). However, leaf thickness, petiole length, leaf area index, and leaf weight ratio were affected non-significantly. But petiole girth was recorded maximum (1.22 and 1.49 mm) under incandescent bulbs which was at par with LED and significantly higher than CFL.